The Facial Platysma and Its Underappreciated Role in Lower Face Dynamics and Contour. Issue 8 (August 2017) - de Almeida, Ada R.T.; Romiti, Alessandra; Carruthers, Jean D.A.
Abstract : BACKGROUND: The platysma is a superficial muscle involved in important features of the aging neck. Vertical bands, horizontal lines, and loss of lower face contour are effectively treated with botulinum toxin A (BoNT-A). However, its pars facialis, mandibularis, and modiolaris have been underappreciated. OBJECTIVE: To demonstrate the role of BoNT-A treatment of the upper platysma and its impact on lower face dynamics and contour. MATERIAL AND METHODS: Retrospective analysis of cases treated by an injection pattern encompassing the facial platysma components, aiming to block the lower face as a whole complex. It consisted of 2 intramuscular injections into the mentalis muscle and 2 horizontal lines of BoNT-A injections superficially performed above and below the mandible (total dose, 16 onabotulinumtoxinA U/side). Photographs were taken at rest and during motion (frontal and oblique views), before and after treatment. RESULTS: A total of 161 patients have been treated in the last 2 years with the following results: frontal and lateral enhancement of lower facial contour, relaxation of high horizontal lines located just below the lateral mandibular border, and lower deep vertical smile lines present lateral to the oral commissures and melomental folds. CONCLUSION: The upper platysma muscle plays a relevant role in the functional anatomy of the lower face that can be modulated safely with neuromodulators.